2007
DOI: 10.1148/radiol.2443061769
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Assessment with Nonenhanced Steady-State Free Precession versus Contrast-enhanced MR Angiography

Abstract: Slab-selective inversion-prepared 3D SSFP MR angiography had high sensitivity, specificity, accuracy, and NPV for RAS detection, without the need for contrast material. However, RAS severity was overestimated in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 22 publications
6
75
1
Order By: Relevance
“…Renal flow-in spin labeling NCE-MRA has been compared to CTA (73) and DSA (74,75) in several clinical studies. Similar to other NCE-MRA techniques, the clinical comparison studies (73)(74)(75) report high sensitivity (100%, 100%, and 93%, respectively) but lower specificity (93%, 88%, and 88%, respectively) for flow-in spin labeling versus Figure 11. Example of renal NCE-MRA using flow-in spin labeling.…”
Section: Applicationsmentioning
confidence: 99%
“…Renal flow-in spin labeling NCE-MRA has been compared to CTA (73) and DSA (74,75) in several clinical studies. Similar to other NCE-MRA techniques, the clinical comparison studies (73)(74)(75) report high sensitivity (100%, 100%, and 93%, respectively) but lower specificity (93%, 88%, and 88%, respectively) for flow-in spin labeling versus Figure 11. Example of renal NCE-MRA using flow-in spin labeling.…”
Section: Applicationsmentioning
confidence: 99%
“…The use of Bal-SSFP for the evaluation of renal arteries has been reported by several investigators with promising results (38,(44)(45)(46)(47)(48)(49). The main advantages of Bal-SSFP are a high signal to noise ratio, T2/T1-weighted image contrast (making blood intrinsically bright independent of flow), speed, and relative flow insensitivity (50,51).…”
Section: Balanced-steady-state Free Precession Mramentioning
confidence: 99%
“…In 2007, Wyttenbach et al reported a much larger 57 patient blinded comparison between an ECG-triggered Bal-SSFP sequence and CE-MRA for the evaluation of the aorta and renal arteries (45). Sequence parameters are shown in Table 2 (Wyttenbach).…”
Section: Ecg-triggered Bal-ssfpmentioning
confidence: 99%
“…While theoretical predictions suggest that greater improvement in FWHM may be obtained with longer scan times, such lengthening of time may not be appropriate for thoraco-abdominal CE-MRA acquisitions due to respiratory motion. Other factors, such as intrinsic motion of the renal arteries associated with cardiac pulsation and diaphragmatic drift during the breath-hold (39,40), may play an important role in limiting the achievable spatial resolution with CE-MRA, and other motion-compensated renal artery angiographic techniques may need to be evaluated (41)(42)(43)(44).…”
Section: Resolution Considerationsmentioning
confidence: 99%